2014
DOI: 10.1175/jas-d-13-0189.1
|View full text |Cite
|
Sign up to set email alerts
|

Wind Shear and Buoyancy Reversal at the Top of Stratocumulus

Abstract: A numerical experiment is designed to study the interaction at the stratocumulus top between a mean vertical shear and the buoyancy reversal due to evaporative cooling, without radiative cooling. Direct numerical simulation is used to eliminate the uncertainty introduced by turbulence models. It is found that the enhancement by shear-induced mixing of the turbulence caused by buoyancy reversal can render buoyancy reversal comparable to other forcing mechanisms. However, it is also found that (i) the velocity j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 48 publications
(52 reference statements)
4
38
1
Order By: Relevance
“…16 therein), who argued that thickness of the CTMSL diminishes with growing CTEI. Similar structure of "classical" non-POST stratocumulus was also reported in numerical simulations of CTEI permitting in the DYCOMS RF01 case by Mellado et al (2014), who demonstrated a "peeling off" of the negatively buoyant volumes from the shear layer at the cloud top.…”
Section: Thickness Of the Sublayerssupporting
confidence: 75%
See 1 more Smart Citation
“…16 therein), who argued that thickness of the CTMSL diminishes with growing CTEI. Similar structure of "classical" non-POST stratocumulus was also reported in numerical simulations of CTEI permitting in the DYCOMS RF01 case by Mellado et al (2014), who demonstrated a "peeling off" of the negatively buoyant volumes from the shear layer at the cloud top.…”
Section: Thickness Of the Sublayerssupporting
confidence: 75%
“…The above relation is equivalent to Eq. (6) in Mellado et al (2014), who analyze the results of numerical simulations of stratocumulus top mixing and adopted estimates of the asymptotic thickness of shear layers in oceanic flows (Smyth and Moum, 2000;Brucker and Sarkar, 2007) and in the cloud-free atmospheric boundary layer (Conzemius and Fedorovich, 2007).…”
Section: Bulk Richardson Numbermentioning
confidence: 99%
“…This analysis does not distinguish between the effects of higher shear production of TKE at higher wind speed at the surface and at the inversion (Fig. 11d), and therefore does not determine whether shear production of TKE at the inversion due to geostrophic wind supports entrainment, as locally generated shear does (Wang et al, , 2012Katzwinkel et al, 2012;Mellado et al, 2014).…”
Section: Buoyancy-and Shear-driven Dynamicsmentioning
confidence: 99%
“…A number of studies (e.g., Wang et al, 2008Wang et al, , 2012Katzwinkel et al, 2012;Mellado et al, 2014) have investigated the effect of strong wind shear at the inversion on stratocumulus clouds. Such shear is often caused by a jump in large-scale wind speed and direction across the inversion, and differs qualitatively and quantitatively from shear that arises from the interaction of a constant large-scale wind speed with the surface and with the potential temperature gradient at the inversion.…”
mentioning
confidence: 99%
“…It is modeled such that it plays a substantial part in mixing near the surface as well as in the entrainment zone. In the entrainment zone, it is designed to mix the warmer air from above the boundary layer into the layer, following for instance, the theoretical arguments of Mellado et al [2014]. The diffusivity also physically incorporates the vertical grid size, and in so doing can help minimize some of the deleterious effects of insufficient vertical resolution.…”
Section: Journal Of Advances In Modeling Earth Systems 101002/2015msmentioning
confidence: 99%